Impact of ESG Scores on Stock Returns : evidence from the European stock market - Magalhães Castro, Rita Nicole; Vyletelka, Michal; Stádník, Bohumil; Vysoká škola ekonomická v Praze. Fakulta financí a účetnictví (2024)
In the past several years, literature has been comprehensively studying the integration of climate change and other sustainability concerns into investment decisions and portfolio allocation, however, the complete impact of these concerns on investment performance is still not fully known. In this sense, the present study analyses the impact of ESG scores and, specifically, ESG scores divergence, at an individual level (environmental, social and governance), on stock returns of the European stock market. For this purpose, 737 European listed companies are considered for the period between January 2015 and March 2022. The results show no significant relationship between Environmental divergence scores and stock returns, contrary to expectations. Additionally, Social and Governance divergence scores exhibit unexpected negative relationships. Furthermore, investing in portfolios with stocks with lower Environmental or Social divergence tends to outperform standard indices, while Governance-focused portfolios generally outperform indices. The addition of more Environmental, Social and Governance scores given by different rating providers might enhance the understanding of this relationship.
Vedoucí práce: Michal Vyletelka
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Fakulta financí a účetnictví, 2024
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2024
Způsob přístupu: Internet
Keywords: finance and accounting [obor dipl. práce]; diplomové práce; master's theses